Predictive value of C-reactive protein in response to macrolides in children with macrolide-resistant pneumonia - Young Ho Seo; Jang Su Kim; Sung Chul Seo; Won Hee Seo; Young Yoo; Dae Jin Song; Ji Tae Choung (Korean Pediatric Society, 2014)
PurposeThe prevalence of macrolide-resistant Mycoplasma pneumoniae (MRMP) has increased worldwide. The aim of this study was to estimate the proportion of MRMP in a tertiary hospital in Korea, and to find potential laboratory markers that could be used to predict the efficacy of macrolides in children with MRMP pneumonia.MethodsA total of 95 patients with M. pneumoniae pneumonia were enrolled in this study. Detection of MRMP was based on the results of specific point mutations in domain V of the 23S rRNA gene. The medical records of these patients were reviewed retrospectively and the clinical course and laboratory data were compared.ResultsThe proportion of patients with MRMP was 51.6% and all MRMP isolates had the A2063G point mutation. The MRMP group had longer hospital stay and febrile period after initiation of macrolides. The levels of serum C-reactive protein (CRP) and interleukin-18 in nasopharyngeal aspirate were significantly higher in patients who did not respond to macrolide treatment. CRP was the only significant factor in predicting the efficacy of macrolides in patients with MRMP pneumonia. The area under the curve for CRP was 0.69 in receiver operating characteristic curve analysis, indicating reasonable discriminative power, and the optimal cutoff value was 40.7 mg/L.ConclusionThe proportion of patients with MRMP was high, suggesting that the prevalence of MRMP is rising rapidly in Korea. Serum CRP could be a useful marker for predicting the efficacy of macrolides and helping clinicians make better clinical decisions in children with MRMP pneumonia.